2011
DOI: 10.1128/aem.02831-10
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Carriage and Shedding Density of CTX-M Extended-Spectrum β-Lactamase-Producing Escherichia coli in Cattle, Chickens, and Pigs: Implications for Environmental Contamination and Food Production

Abstract: The number and proportion of CTX-M positive Escherichia coli organisms were determined in feces from cattle, chickens, and pigs in the United Kingdom to provide a better understanding of the risk of the dissemination of extended-spectrum ␤-lactamase (ESBL) bacteria to humans from food animal sources. Samples of bovine (n ‫؍‬ 35) and swine (n ‫؍‬ 20) feces were collected from farms, and chicken cecal contents (n ‫؍‬ 32) were collected from abattoirs. There was wide variation in the number of CTX-M-positive E. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
81
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 36 publications
14
81
0
2
Order By: Relevance
“…LREC215, a commensal E. coli isolated from a broiler chick (Horton et al, 2011), and LREC447, an avian pathogenic E. coli isolated from a broiler (Randall et al, 2012), were confirmed by PCR to carry a CTX-M group 1 gene on an IncI1-g plasmid and to be sensitive to kanamycin, a strong selectable marker present in pIFM27. Electrocompetent cells were transformed with curing vector pIFM27 with selection on kanamycin (50 mg l À1 ).…”
Section: Construction Of the Inci1 Curing Plasmid: Selection Of Targementioning
confidence: 99%
See 3 more Smart Citations
“…LREC215, a commensal E. coli isolated from a broiler chick (Horton et al, 2011), and LREC447, an avian pathogenic E. coli isolated from a broiler (Randall et al, 2012), were confirmed by PCR to carry a CTX-M group 1 gene on an IncI1-g plasmid and to be sensitive to kanamycin, a strong selectable marker present in pIFM27. Electrocompetent cells were transformed with curing vector pIFM27 with selection on kanamycin (50 mg l À1 ).…”
Section: Construction Of the Inci1 Curing Plasmid: Selection Of Targementioning
confidence: 99%
“…The strains and plasmids described in this study were either WT and originating from previous studies (Freire Martín et al, 2014;Horton et al, 2011;Randall et al, 2012), commercially available strains and plasmids or, in the case of pIFM26 (S1), a modification of previously described plasmid pAKE604 (El-Sayed et al, 2001), which differed from it only in the orientation of the restriction sites within its multiple cloning site. The strains were grown in LB medium and, when necessary for plasmid maintenance, in the presence of appropriate antibiotics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of bla CTX-M has been detected in food animal populations [3], food products [4], and both domestic [5] and wild [6] animal species throughout the world. Saudi Arabia is one of many countries with higher rates of bacterial pathogens with ESBLs-producers in the clinical setting, mostly associated with CTX-M-types [7,8].…”
Section: Introductionmentioning
confidence: 99%